Opposite effects of statins on mitochondria of cardiac and skeletal muscles: a 'mitohormesis' mechanism involving reactive oxygen species and PGC-1 - Bouitbir, Jamal; Charles, Anne-Laure; Echaniz-Laguna, Andoni; Kindo, Michel; Daussin, Frédéric; Auwerx, Johan; Piquard, François; Geny, Bernard; Zoll, Joffrey (European heart journal, 2012)
Statins protect against cardiovascular-related mortality but induce skeletal muscle toxicity. To investigate mechanisms of statins, we tested the hypothesis that statins optimized cardiac mitochondrial function but impaired vulnerable skeletal muscle by inducing different level of reactive oxygen species (ROS). In atrium of patients treated with statins, ROS production was decreased and oxidative capacities were enhanced together with an extensive augmentation of mRNAs expression of peroxisome proliferator-activated receptor gamma co-activator (PGC-1) family. However, in deltoid biopsies from patients with statin-induced muscular myopathy, oxidative capacities were decreased together with ROS increase and a collapse of PGC-1 mRNA expression. Several animal and cell culture experiments were conducted and showed by using ROS scavengers that ROS production was the triggering factor responsible of atorvastatin-induced activation of mitochondrial biogenesis pathway and improvement of antioxidant capacities in heart. Conversely, in skeletal muscle, the large augmentation of ROS production following treatment induced mitochondrial impairments, and reduced mitochondrial biogenesis mechanisms. Quercetin, an antioxidant molecule, was able to counteract skeletal muscle deleterious effects of atorvastatin in rat. Our findings identify statins as a new activating factor of cardiac mitochondrial biogenesis and antioxidant capacities, and suggest the importance of ROS/PGC-1 signalling pathway as a key element in regulation of mitochondrial function in cardiac as well as skeletal muscles.